Antimicrobial Activity of Acidophilic Actinomycetes Isolated from Acidic Soil - Niyasom*, Chaisit; Boonmak, Sawitree; Meesri, Nutsara (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Acidophilic actinomycetes were isolated from acidic soil samples on Starch Casein Agar, Soil Extract Agar and Humic Vitamin Agar, pH 4.5, containing nystatin and nalidixic acid. The total acidophilic actinomycete counts ranged from 3.9-8.2 x 103 CFU/g of soil sample. Antibacterial activities of isolated actinomycetes were primarily screened by agar plug method. Three isolates exhibited antibacterial activity against all 4 tested bacteria, which were Bacillus cereus, Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus. Furthermore, 10 isolates showed antifungal activity against Fusarium sp., Curvularia sp. and Colletotrichum gloeosporioides. The 14-day YM culture broth and mycelium of isolate AA01 and AA02 were extracted with hexane, ethyl acetate and methanol. The crude extracts of AA01 and AA02 were then tested for antibacterial and antifungal activity, respectively. The MIC values of methanolic crude extract from AA01 against B. cereus, P. aeruginosa, E. coli and S. aureus were 5, 20, 40 and 5 mg/ml, respectively. The methanolic crude extract from AA02 at concentration of 30 mg/ml can inhibit at least 50% of the fungal growth. Keywords: acidophilic actinomycete, antibacterial activity, antifungal activity, acidic soil. *Corresponding author: nchaisit@yahoo.com